Web-based Content Management System For SMIL-Based Interactive Multimedia Content - Cheong, Soon Nyean (2007)
This project aims to allow collaboration between geographically distributed publishing staff. Up to this point, there has been very little research done on creating a system that allows remote creation, integration and management of SMIL-based interactive multimedia news.